Functionalized separator for next-generation batteries. (December 2020) - Huang, Xiaozhou; He, Rui; Li, Matthew; Chee, Mason Oliver Lam; Dong, Pei; Lu, Jun
Graphical abstract: Abstract: Advancements in battery technology have dramatically increased demand for improvements in separator design, as the separator plays a critical role in ensuring the safety and electrochemical performance of the cells. Current separators, either in commercial usage or under investigation, have yet to meet the high stability and lifespan performance standards necessary to prevent deterioration in the efficiency and reliability of the battery technologies. Recently, considerable effort has been devoted to developing functionalized separators, ranging from designing a variety of new materials and modification methods, and increasingly, to optimizing advanced preparation processes. In order to understand how the mechanisms of separator performance are affected by different properties, we will first summarize recent research progress and then have in-depth discussions regarding the separator's significant contribution to enhancing the safety and performance of the cell. We then provide our design strategy for future separators, which not only meets the requirements of different type of batteries, but also aims for multifunctionality. We hope such a perspective could provide new inspiration in the development of separator research for future battery technologies.